2019
DOI: 10.1039/c9fo01616c
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin promotes bile acid metabolism and reduces hepatic cholesterol deposition by inhibiting the farnesoid X receptor (FXR)-mediated enterohepatic axis

Abstract: Lactoferrin (LF) is a multifunctional glycoprotein that can regulate lipid metabolism, lower cholesterol, reduce body weight, and prevent atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…As CYP7A1 is a rate-limiting step for bile acid synthesis and CYP8B1 determines the synthetic flow of cholesterol in hepatocytes, regulating the expression levels of these proteins altered the amount and profile of biosynthetic cholesterol [ 8 ]. The results of the current study are consistent with reports indicating that hepatic CYP7A1 and CYP8B1 expression are lowered in diet-induced hyperlipidemia models and that FGF15/19 suppressed expression of both these genes [ 44 , 45 ]. Recently, the pharmacological induction of distal intestinal FGF15/19 led to hepatic bile acid metabolism and further enhanced fecal cholesterol excretion in combination with ezetimibe, a TICE inducer [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…As CYP7A1 is a rate-limiting step for bile acid synthesis and CYP8B1 determines the synthetic flow of cholesterol in hepatocytes, regulating the expression levels of these proteins altered the amount and profile of biosynthetic cholesterol [ 8 ]. The results of the current study are consistent with reports indicating that hepatic CYP7A1 and CYP8B1 expression are lowered in diet-induced hyperlipidemia models and that FGF15/19 suppressed expression of both these genes [ 44 , 45 ]. Recently, the pharmacological induction of distal intestinal FGF15/19 led to hepatic bile acid metabolism and further enhanced fecal cholesterol excretion in combination with ezetimibe, a TICE inducer [ 10 ].…”
Section: Discussionsupporting
confidence: 92%
“…The Lf doses in clinical trials ranged from 200 to 3600 mg day −1 , [ 30–35 ] and mainly concentrated in 1 g day −1 , [ 31–34 ] which is equal to decuple daily dose. In the previous studies, the Lf intervention doses were usually very high, [ 12,19,21 ] whereas the effects of Lf at daily dose on disease prevention have not been fully determined. Considering the ethanol‐caused potential risks of food consumption reduction and malnutrition, [ 22 ] we used AIN‐93G as the control diet and elevated Lf proportion in total protein.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies on the health‐protective effects of Lf, the intervention doses were too high to reach via normal diet. [ 12,19–21 ] Additionally, Lf was usually administrated as an additional supplement instead of replacing the dietary basic protein, which could not exclude the effects of additional protein supplement on disease prevention.…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] In the liver, activated FXR induces the expression of SHP, which inhibits the expression of CYP7A1 in transcriptional level. [ 39 ] A previous study found that anthocyanins increased mRNA expression of CYP7A1 in liver and activated the conversion of cholesterol to bile acids in hamsters. [ 40 ] Primary bile acid, namely cholic acid and chenodeoxycholic acid, can be transformed into secondary bile acids (deoxycholic acid, lithocholic acid) by bacterial metabolites.…”
Section: Discussionmentioning
confidence: 99%